SUSTAINABLE FINANCIAL GOVERNANCE : TAX COLLECTION AND MODERATING ROLE OF TAX AVOIDANCE IN CRYPTOCURRENCY ASSET - Komang Widhya Sedana Putra P; Ni Wayan Lasmi (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2024)
The main objective of this investigation is to assess the impact of tax implementation on cryptocurrency asset exchanges, with tax avoidance as a moderating variable, in the context of Indonesia. The study population involves individuals actively engaged in crypto investments, possessing operational crypto accounts, and maintaining records of crypto transactions, totaling 100 respondents. The analytical framework includes various assessments, including Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, Determination Coefficient Test, F Test, and t Test. The research findings reveal that tax implementation has a significant and negative impact on cryptocurrency asset transactions. Conversely, tax avoidance demonstrates a substantial positive influence in moderating the relationship between the two variables.